Evaluation of the effect on antimicrobial properties, color, roughness and curing time of glass ionomer cement incorporated with silver and copper nanoparticles - Laís Aragão Lima; Wanessa Fernandes Matias Regis; Fábio Ruan Louzeiro Lima; Victor Teixeira Noronha; Amauri Jardim de Paula; Fernanda Freitas Sousa; Paulo Goberlânio Barros Silva; Rafael Melo Freire; Lidiany Karla Azevedo Rodrigues (Discover Materials)
Abstract The objective of this study was to investigate the antimicrobial potential of glass ionomer cement (GIC) incorporated with silver and copper nanoparticles (CuAgNP) in three different concentrations (GIC 0.01% CuAgNP, GIC 0.05% CuAgNP, and GIC 0.1% CuAgNP) on the inhibition of in vitro formation of duospecies biofilm of Streptococcus mutans and Candida albicans, surface roughness, color variation, and curing time. A control group was also included, consisting of GIC without nanoparticles. Duoespecie biofilms were grown on specimens of GIC in Tryptic Soy Broth placed in 24-well plates for 72 h. The biofilms were then collected and plated on Mitis-Salivarius-Bacitracin (MSB) agar and Sabouraud dextrose agar for Streptococcus mutans and Candida albicans, respectively. Colony-forming unit (CFU) counts and dry weight were measured to assess the biofilm growth. Physical properties were evaluated through tests on surface roughness, color variation, and curing time. The normality of the distribution was evaluated using the Kolmogorov–Smirnov test. Data were analyzed using ANOVA followed by Tukey’s test. The results showed that the addition of CuAgNP did not increase antimicrobial activity compared to the control (p > 0.05). Furthermore, longer curing time resulted in negative effects on physical properties, such as color variation and greater surface roughness (p < 0.05). The addition of CuAgNP did not improve the properties of GIC in this study.